SMALL INDUSTRIES DEVELOPMENT OBSTACLES IN KANAGARIAN PADANG TAROK AGAM DISTRICT OF BASO - Marlena, Syahri - (Pendidikan Geografi, 2014)
This study aims to reveal emperi late, analyze the data about the relationship between capital, raw materials, labor and marketing to small business development in Padang Kanagarian Tarok Agam District of Baso.This study classified descriptive correlational research, look for relationships between variables, namely the relationship between capital (X1), raw materials (X2), labor (X3) and marketing (X4) with the development of the industry (Y). Research is the entire population of a small industrial entrepreneurs in Padang Kanagarian Tarok and samples were taken by using a sampling technique which amounts to a total of 30 industry employers, means of data collection in this study questionnaire, before the questionnaires were distributed to the entire study sample.The results of this study, (1) There is a significant and positive relationship between the capital with little industrial development in the district of Padang Tarok Baso Kanagarian Agam District. Capital analysis of variance of 36.8% for industrial development contribute, (2) a significant relationship and feedstock positifantara with the development of small industries in Padang Kanagarian Tarok Agam District of Baso. Analysis of variance of raw materials contributed 82.2% to the industrial development variables. (3) There is a significant and positive relationship between the workers and the development of small industries in Padang Kanagarian Tarok Agam District of Baso. Employment Analysis of variance contributed 13.6% towards the development of the industry. (4) There is a significant and positive relationship between marketing to small business development in Padang Kanagarian Tarok Agam District of Baso. Marketing Analysis of variance contributed 18.1% towards the development of the industry. (5) capital, raw materials, labor and marketing together 88.9% influence on the development of the industry.